PURCHASE INTENTION BEHAVIOR IN CO-BRANDING PRODUCTS WITH SOCIAL MEDIA AS A MODERATING VARIABLE - Sumantri, Dadan; Fahmi, Radiyul; Fathurrohman, Firdaus; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Mulyadi, Hari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to investigate the influence of co-branding on consumer attitudes and purchase intentions, with social media as a moderating variable. This study focuses on the Hard13 Noir Low and High co-branded products, with a sample of 200 respondents selected using purposive sampling. The data was collected through a questionnaire distributed online using Google Forms and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The research results show that product and brand fit positively and significantly influence attitudes towards co-branded products. Attitudes toward co-branded products have also significantly influenced consumer purchasing intentions. In addition, social media was found to strengthen the relationship between product fit and brand fit with attitudes towards co-branded products and the relationship between attitudes towards co-branded products and purchase intentions. These findings can help companies manage the co-branding strategy, develop more effective marketing strategies, and suggest that using the social media can increase the consumer buying interest, especially as they face dynamic market challenges in the digital and post pandemic era.JEL: M3, O3.